PENDAMPINGAN PENGELOLAAN KEUANGAN PADA PELAKU UMKM KELURAHAN TAMANSARI KECAMATAN PULOMERAK, KOTA CILEGON - Ulfi Jefri; Rika Kartika; Ratu Sifa Ni’mah; Raden Irna Afriani; Yuliah Yuliah (Jurnal Abdimas Bina Bangsa, 2023)
This community service aims to support micro, small and medium enterprises (MSMEs) in managing the financial reports of the businesses they run. Micro businesses, especially in the Tamansari sub-district, Pulo Merak sub-district, Cilegon city. Financial statements are one of the important components that must be owned by MSME actors. This is also widely carried out in the household environment, in order to supplement income or even as the main source of household income. Likewise, in Tamansari Village, Pulomerak District, the majority of the people's livelihood is trading. Various types of business carried out by local residents. Of course, in running a business, it is necessary to have financial management so that business owners are able to know the amount of profit earned. However, the local community's ability to manage financial businesses is minimal, making it difficult to distinguish venture capital and profit when earning income from a business. Based on these conditions, community service is carried out to provide knowledge about financial management and preparing financial reports in a simple way so that you can know the amount of profit. This community service uses the seminar method which takes place at the Tamansari Village Office with participants from MSME actors in the community around the Tamansari Village office. The results of this community service activity can increase knowledge about financial management and preparation of simple financial reports and implement the preparation of financial reports for Micro, Small and Medium Enterprises (MSMEs) in Tamansari Village